2016
DOI: 10.1016/j.jpainsymman.2016.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Home Care Reduces Hospice Disenrollment and Hospitalization After Hospice Enrollment

Abstract: Objectives To identify hospice and patient characteristics associated with the use of continuous home care (CHC), and to examine the associations between CHC utilization and hospice disenrollment or hospitalization after hospice enrollment. Methods Using 100% fee-for-service Medicare claims data for beneficiaries aged 66 years or older who died between July and December 2011, we identified the percentage of hospice agencies in which patients used CHC in 2011 and determined hospice and patient characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
1
9
1
Order By: Relevance
“…Our results build upon and support a previous study that found CHC reduced hospice disenrollment and hospitalization. 11 Our findings reiterate that the use of CHC or GIP care by hospices is associated with a reduction in odds of a hospitalrelated disenrollment. Further research is needed to understand how to best utilize and promote these resources when they are needed.…”
Section: Discussionsupporting
confidence: 64%
“…Our results build upon and support a previous study that found CHC reduced hospice disenrollment and hospitalization. 11 Our findings reiterate that the use of CHC or GIP care by hospices is associated with a reduction in odds of a hospitalrelated disenrollment. Further research is needed to understand how to best utilize and promote these resources when they are needed.…”
Section: Discussionsupporting
confidence: 64%
“…Evidence exists that the provision of continuous home care decreases the number of hospitalizations in hospice patients, but other interventions for decreasing acute care use should be evaluated. 32 We were surprised to note that almost a fifth of hospice patients in our sample lacked an advance directive. While hospice is often seen as a choice against pursuing aggressive care, we are not certain that all patients and families understand that or have reached consensus on that point.…”
Section: Discussionmentioning
confidence: 81%
“…In this study, we found that hospices that provided CHC services had lower rates of hospice disenrollment or hospitalization than hospices which did not provide CHC services. Previous evidence has suggested that within CHC hospices, hospice enrollees who use CHC services may have better outcomes, including a decrease in hospice disenrollment or hospitalization at the end of life 1113 . Prior studies, however, analyzed data of CHC hospice enrollees only and were unable to examine whether hospice’s offering of CHC may mitigate risks of disenrollment and hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggested that the percentage of hospice enrollees who received CHC differed substantially across CHC hospices and, in some hospices, exceeded 75% 13, 22 . There have been concerns about overuse of healthcare services in the United States 23 ; and there have been potential fraud hospice claims 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation